2002
DOI: 10.1128/aem.68.7.3651-3654.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a Gene Encoding Raw-Starch-Digesting Amylase from a Cytophaga sp. and Its Expression in Escherichia coli

Abstract: A raw-starch-digesting amylase (RSDA) gene from a Cytophaga sp. was cloned and sequenced. The predicted protein product contained 519 amino acids and had high amino acid identity to ␣-amylases from three Bacillus species. Only one of the Bacillus ␣-amylases has raw-starch-digesting capability, however. The RSDA, expressed in Escherichia coli, had properties similar to those of the enzyme purified from the Cytophaga sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Thus, the raw-starch-hydrolyzing enzymes have gained much importance for effective utilization of natural resources since they also overcome viscosity problems (Jeang et al 2002). The experiments in the present study proved a strong correlation between the adsorption and hydrolysis rates.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, the raw-starch-hydrolyzing enzymes have gained much importance for effective utilization of natural resources since they also overcome viscosity problems (Jeang et al 2002). The experiments in the present study proved a strong correlation between the adsorption and hydrolysis rates.…”
Section: Discussionsupporting
confidence: 56%
“…There was a previous report on cloning and sequencing of raw-starch-digesting amylase from a Cytophaga sp. (Jeang et al 2002), which showed high amino acid identity with the α-amylases from three Bacillus sp. (Southgate et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity between the two groups implies an evolutionary relationship, as observed previously for a cluster of bacterial enzymes with similarity to animal aamylases, suggested to be a result of horizontal gene transfer (Da Lage et al, 2004). The bacterial a-amylases belonging to subfamily GH13_5 include enzymes from Bacillus and Cytophaga species (Yuuki et al, 1985;Jeang et al, 2002;Kanai et al, 2004), some of which are thermostable (Kim et al, 2000) and used in industry (Guzman-Maldonado & Paredes-Lopez, 1995). Several of these bacterial enzymes are known to produce oligosaccharides of specific lengths from starch, including, for example, a maltohexaose-forming a-amylase from Bacillus (Kanai et al, 2004).…”
Section: Discussionmentioning
confidence: 74%
“…It was reported that, the rsda gene of a Cytophaga sp. was cloned and expressed in E. coli DH5α and the enzyme was produced intracellularly by the transformant 39 . Similarly, the Bacillus subtilis β-1,4-glucanase gene (a similar enzyme hydrolyzing β-1,4-linkages present in noncrystalline cellulosic substrates such as carboxymethyl cellulose and trinitrophenyl carboxymethyl cellulose) was cloned in E. coli expressing the intracellularly 40 .…”
Section: Discussionmentioning
confidence: 99%